Analysis Of Financial Performance And Strategies For Increasing The Minimum Core Capital Of Bank BPD In Accordance With The Provisions Of Pojk No. 12/Pojk.03/2020 - Esty Rahayu, Nur Ellyanawati (JURNAL ILMU MANAJEMEN, 2025)
This study aims to analyze the financial performance and strategies for increasing the core capital of Pembangunan Daerah (BPD) Banks in accordance with the Financial Services Authority of Indonesia (OJK) Regulation No. 12/POJK.03/2020 concerning the Consolidation of Commercial Banks, which stipulates a minimum core capital of IDR 3 trillion by 2024. The financial performance assessment was carried out using the CAMEL, RGEC, and Altman Z-Score models. The research employed a descriptive-comparative approach. The observation period covered 2023–2024 with a sample of ten BPD Banks categorized under Core Capital Group 1. The CAMEL analysis indicates that Bank Sultra, Bank Sulteng, Bank NTB Syariah, Bank SulutGo, and Bank Bengkulu fall within the sound category, while the other five (5) BPDs are categorized as fairly sound. The RGEC analysis shows that Bank Sultra, Bank NTB Syariah, Bank NTT, Bank BJB Syariah, Bank Malulu Malut, Bank Bengkulu, and Bank Banten are deemed sound, whereas the other three (3) BPD banks are assessed as fairly sound. The Altman Z-Score results show that nine (9) BPD banks are financially sound, with only Bank Banten positioned within the grey area. Strategies to enhance the core capital of BPDs can be pursued through: (a) increasing local government shareholding; (b) consolidating with BPDs in Core Capital Groups 2 or 3; (c) consolidating with other BPDs in Core Capital Group 1; (d) attracting investment from state-owned banks (BUMN) or private banks; (e) engaging non-bank investors, both domestic and international; and (f) conducting a rights issue for BPDs already listed on the Indonesia Stock Exchange.